Dehydration of carbohydrates into 5-hydroxymethylfurfural over vanadyl pyrophosphate catalysts. (February 2021) - Najafi Sarpiri, Jaleh; Najafi Chermahini, Alireza; Saraji, Mohammad; Shahvar, Ali
Abstract: The catalytic activity of a series of vanadyl pyrophosphate (VPP) catalysts with different loadings supported on mesoporous silica KIT-6 was investigated for the dehydration of glucose and fructose into 5-hydroxymethylfurfural (5-HMF). The active phase was synthesized by V2 O5 reduction in an alcoholic media followed by calcination of VOHPO4 .0.5H2 O precursor at 400 °C. The catalysts were characterized by FT-IR spectroscopy, Raman spectroscopy, ICP-OES, X-ray diffraction (XRD), N2 adsorption-desorption analysis, and temperature-programmed desorption (NH3 -TPD) techniques as well as SEM, TEM, and X-ray photoelectron spectroscopy (XPS). Among the catalysts, the one containing the lowest percentage of VPP exhibited the best activity in the dehydration reaction. The effect of different parameters such as the loading amount of VPP on the support, the initial amount of carbohydrates and catalyst, reaction temperature, time, and solvent was studied. The highest yields of 5-HMF were obtained to be 79% (145 °C/1 h) and 48% (185 °C/1.5 h) for the fructose and glucose dehydration, respectively. Catalysts were simply separated via centrifugation without significant changes in catalytic activity and reused for additional four runs. Graphical abstract: Image 1 Highlights: Vanadyl pyrophosphate catalysts over mesoporous KIT-6 were synthesized with different loading amounts. Their catalytic activity evaluated in the dehydration of glucose and fructose into 5-hydroxymethylfurfural. The catalyst with the highest surface area showed the most 5-hydroxymethylfurfural yield. The selected catalyst was recycled four times with no significant decrease in catalytic activity.